Do non-monetary prices target the poor? Evidence from a field experiment in India - Bridget Hoffmann (Inter-American Development Bank (IDB), 2016)
This paper uses willingness to pay (WTP) data from a field experiment in Hyderabad, India in 2013 to determine whether non-monetary prices better target health products to the poor than monetary prices. Monetary WTP is increasing in income and non-monetary WTP is weakly decreasing in income. Household fixed effects in a pooled sample of monetary WTP and non-monetary WTP are used to compare the correlation of income and WTP across price types. It is found that non-monetary WTP falls relative to monetary WTP as income rises. Finally, a greater fraction of demand is comprised of the poor at non-monetary prices.
hdl:11319/7862
Keywords: O12; H42; D61; I14; I15; C93; 330; Non-monetary price; Ordeal mechanism; Targeting; Subsidies